Selenium intake and selenium blood levels: a novel food frequency questionnaire - Pestitschek, Marianne; Sonneck-Koenne, Charlotte; Zakavi, S. R.; Li, Shuren; Knoll, Peter; Mirzaei, Siroos (Wiener Klinische Wochenschrift, 2013)
Summary Aim The present study was undertaken to estimate the selenium intake of thyroid patients and investigate the possible relation between thyroid abnormalities and the selenium intake. Methods The selenium intake through foods and the nutritional habits of thyroid patients in general were analyzed. Total 212 subjects from thyroid outpatient clinic of two state hospitals were interviewed. Among 212 subjects, 21 had no thyroid abnormality and served as controls. A food frequency questionnaire (FFQ) was developed to define the individual selenium intakes. From five different food groups, a total of 15 selenium-rich foods were selected, which are obtainable in Austria. The clinical and nutritional data were analyzed. Results Animal products such as milk and meat (pork, beef and poultry) played the most important role for the selenium supply in the Austrian diet. The intake of selenium in 86 % of the total study population was below the estimated average requirement (EAR). The selenium level was higher in euthyroid people compared with hypothyroid patients. Conclusions The developed FFQ is a tool to estimate the selenium intake in individuals, as it could be shown in this study. A significant positive correlation between selenium intake and blood selenium level was noted. These results must be confirmed by further studies in larger patient population.